STIGMA SOSIAL TERHADAP NARAPIDANA LANSIA DAN DAMPAKNYA TERHADAP KUALITAS HIDUP - Subroto, Mitro; Ubaidillah S, Nur Hakim (Ensiklopedia of Journal, 2024)
This study explores the social stigma faced by elderly prisoners and its impact on their quality of life. The urgency of this research arises from the increasing number of elderly individuals in correctional facilities, coupled with societal misconceptions that exacerbate their isolation and suffering. Employing a qualitative approach, data were collected through interviews and observations, focusing on the lived experiences of elderly inmates. The findings reveal that social stigma significantly diminishes their self-esteem and mental well-being, leading to a lower quality of life. This research underscores the need for policies aimed at reducing stigma and improving support systems for elderly prisoners, ultimately fostering a more inclusive society.Keywords: social stigma; elderly prisoners; quality of life; mental well-being; support systems.